Pengaruh Kualitas Pelayanan Terhadap Loyaltas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Di Fun House Resto - Chandra Gita; Esti Dwi Rahmawati; Rayhan Gunaningrat (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The growing subsector of the food and beverage industry, including the highly competitive restaurant industry, highlights the importance of research in maintaining businesses and increasing customer loyalty in this sector. The purpose of this research is to investigate the influence of service quality on customer loyalty through customer satisfaction as a mediator in Fun House Resto. The method used is the Partial Least Squares - Structural Equation Modeling (PLS-SEM) analysis technique with descriptive and quantitative analysis. The sample used was 100 respondents using purposive sampling method in determining the respondents. The results of the study indicate that service quality has a direct positive effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, and service quality has a positive and significant effect on customer loyalty through mediation of customer satisfaction. These results indicate that Fun House Resto should consider maintaining service quality and customer satisfaction in ensuring customer loyalty. Furthermore, as part of their efforts to maintain customer loyalty, they should also consider other factors such as product quality, facilities, prices, and others.